Comparative Analysis of Production Price Calculation (HPP) Using Activity Based Costing (ABC) and Full Costing (FC) Methods at Tahu Putra Kember Factory - Lastri Yulianti; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
This study was conducted to assess and compare production costing approaches, namely activity-based costing and full costing, in setting product selling prices to avoid errors in setting selling prices that can arise in the company environment. This research method applies a comparative descriptive approach at Mr. Rahmat’s Putra Kembar Tofu Factory. Using a purposive sampling technique, this study collected data on raw material costs, direct labor costs, and factory overhead costs. Data collection was done through interviews, observation, and documentation. The results showed that the cost of goods produced per piece of white tofu, when calculated using the activity-based costing method, amounted to Rp287, while the full costing method amounted to Rp319. For yellow tofu, the cost of production per piece with the activity-based costing method is Rp250, while the full costing method is Rp265. Thus, the activity-based costing method considers overhead costs based on activities in the production process, while the full costing method considers all production costs. As a result, the activity-based costing method proved to be more profitable, with a significant comparison.